Absorption of poorly water soluble drugs subject to apical efflux using phospholipids as solubilizers in the Caco-2 cell model - Kapitza, Susanne B.; Michel, Bettina R.; van Hoogevest, Peter; Leigh, Mathew L.S.; Imanidis, Georgios (European journal of pharmaceutics and biopharmaceutics, 2007)
The purpose of this work was to determine the influence of liposomal solubilization of poorly water soluble drugs exhibiting apical efflux on permeation kinetics and cell toxicity in Caco-2 cells. The HIV-protease inhibitors indinavir and saquinavir were incorporated in phosphatidylcholine liposomes at maximal drug-to-lipid mass ratios and their absorption was determined in Caco-2 cell cultures grown on Transwell inserts using purely aqueous drug solutions as reference. A novel mathematical model was developed to quantitatively delineate the contribution of passive membrane permeation and carrier mediated efflux to transport across the cell monolayer and passive permeability coefficient and maximal efflux rate and affinity constant of the transporter system were determined. Cell toxicity of phospholipids was evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2 H-tetrazolium bromide (MTT) and the lactate dehydrogenase (LDH) assay. Cell integrity was not significantly affected by phospholipid concentrations of up to 150 mg/ml with respect to the used standard tests. Maximum drug concentration was increased 10- and 750-fold for indinavir and saquinavir, respectively, by the use of liposomes. The passive membrane permeability coefficient differed between the two drugs in accordance with their lipophilicity and the affinity for apical efflux transporters was on average 4-fold greater for saquinavir than for indinavir. Liposomal solubilization diminished the passive permeability coefficient of both drugs but the passive apical-to-basal delivery rate was increased by the liposomes compared to the purely aqueous solutions at maximal donor concentrations for at least one of the two drugs. Efflux rate reached a maximum for the liposomal formulations reflecting transporter saturation. Hence, liposomal solubilization considerably increased drug concentration in the media and altered absorption behavior by affecting both the passive diffusion and the carrier mediated efflux components of cell monolayer permeation.